1993
DOI: 10.1007/bf00009729
|View full text |Cite
|
Sign up to set email alerts
|

Light and electron microscopical description of Ceratomyxa labracis n. sp. and a redescription of C. diplodae (Myxosporea: Bivalvulida) from wild and cultured Mediterranean sea bass Dicentrarchus labrax (L.) (Teleostei: Serranidae)

Abstract: Two species of Ceratomyxa (Myxosporea: Bivalvulida) were found in the bile and gall-bladder of wild and cultured Mediterranean sea bass Dicentrarchus labrax. C. labracis n. sp. is described with fine, long lateral processes. The second species is determined as C. diplodae Lubat, Radujkovic, Marques & Bouix, 1989 and redescribed in absence of an adequate original description. Their taxonomic affinities with other species of the genus are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 17 publications
0
15
1
Order By: Relevance
“…The myxospores studied here presented similar measurements to those reported in the description from D. labrax, further coinciding with the observation of different shapes: myxospores are frequently crescentshaped, occasionally arcuate, with the rare occurrence of abnormal forms with 3 valves and 3 polar capsules. The only difference between this and the previous report is the number of polar filament coils, which are 3 to 4 according to the observations of Sitjà-Bobadilla & Álvarez-Pellitero (1993b). Here, the combined use of LM and TEM revealed the polar filament forming 8 to 9 coils organized in 2 rows.…”
Section: Discussioncontrasting
confidence: 46%
See 3 more Smart Citations
“…The myxospores studied here presented similar measurements to those reported in the description from D. labrax, further coinciding with the observation of different shapes: myxospores are frequently crescentshaped, occasionally arcuate, with the rare occurrence of abnormal forms with 3 valves and 3 polar capsules. The only difference between this and the previous report is the number of polar filament coils, which are 3 to 4 according to the observations of Sitjà-Bobadilla & Álvarez-Pellitero (1993b). Here, the combined use of LM and TEM revealed the polar filament forming 8 to 9 coils organized in 2 rows.…”
Section: Discussioncontrasting
confidence: 46%
“…The few exceptions usually produce lesions characterized by vacuolization, deformation, and necrosis of the gall bladder epithelial cells, as has been described for the infection of Ceratomyxa spp. in D. labrax, C. puntazzi in D. puntazzo, and C. dehoopi Reed et al, 2007 in Clinus superciliosus (Linnaeus, 1758) (Álvarez-Pellitero & Sitjà-Bobadilla 1993b, Reed et al 2007, Alama-Bermejo et al 2011). In the case of C. diplodae, Katharios et al (2007) reported high mortalities of D. puntazzo due to heavy infestations of the parasite in potentially immunosuppressed specimens, and Merella et al (2005) correlated C. diplodae with the enlargement of the gall bladder in fish intensively infected with the polyopisthocotylean Atrispinum salpae (Parona & Perugia, 1890).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Traditional bivalvulidan classification based on spore morphology alone to distinguish between closely related species is difficult due to the paucity of informative characters at the light microscopic level and the plasticity of spores Heiniger et al 2008;Sitja-Bobadilla and Alvarez-Pellitero 1993;Meglitsch 1960). Usually genetic variation is combined with morphological and/or biological differences to provide evidence for the recognition of novelty.…”
Section: Recognition Of Speciesmentioning
confidence: 99%